A Reward-Based Behavioral Platform to Measure Neural Activity during Head-Fixed Behavior - Micallef, Andrew H.; Takahashi, Naoya; Larkum, Matthew E.; Palmer, Lucy M. (Frontiers in Cellular Neuroscience, 2017)
Understanding the neural computations that contribute to behavior requires recording from neurons while an animal is behaving. This is not an easy task as most subcellular recording techniques require absolute head stability. The Go/No-Go sensory task is a powerful decision-driven task that enables an animal to report a binary decision during head-fixation. Here we discuss how to set up an Arduino and Python based platform system to control a Go/No-Go sensory behavior paradigm. Using an Arduino micro-controller and python-based custom written program, a reward can be delivered to the animal depending on the decision reported. We discuss the various components required to build the behavioral apparatus that can control and report such a sensory stimulus paradigm. This system enables the end user to control the behavioral testing in real-time and therefore it provides a strong custom-made platform for probing the neural basis of behavior.